TO THE 100th ANNIVERSARY OF PROFESSOR O.K. KOZMINYKH - V. O. Kozminykh; E. N. Kozminykh (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2019)
In connection with the 100th anniversary of Professor Oleg Kozmich Kozminykh, the brief biographical data are presented herein. O.K. Kozminykh made a great contribution to the development of pharmaceutical education and science in the Urals being the leader of Perm Pharmaceutical Institute for more than 20 years. Based on documents and personal memories, the biographical essay is provided and general data of life as well as scientific, pedagogical and public activities of O.K. Kozminykh are summarized here.